Câmara para maturação de salame com controle de temperatura e umidade - Costa, Fabiano Reis da (2014)
The control of temperature, relative humidity, and air circulation of fermented food such as salami is one of the greatest difficulties found during its processing. Salami, which is widely sold nowadays and with great perspectives of commercial expansion, is a handcrafted product from small properties in the legislation. However, it is essential for the quality and it flavor of the product that it is produced according to Produce Safety Standards. The project of the maturation chamber demonstrated in this paper has the objective of changing a commercial refrigerator, whose initial use aimed at food conservation, in an equipment which is able to control temperature and humidity. The variables are controlled by an electronic board Arduino, which aims to provide an easy platform for the development of projects using a micro controller it is part of the physical computing area of computing in which software interacts with the hardware directly, making it possible easy integration of sensors and motors so that it is possible to maintain the necessary variables for the maturation of sausage products in this case.